Translation and Science - Sarukkai, Sundar (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractBoth the discourse and practice of science are fundamentally related to the idea of translation. The multi-semiotic nature of scientific texts makes this explicitly visible. Even at the foundational level, science is possible only because it sees the world as the given original; the response of science to the original-world shares common features with the concerns of translation. In this paper, the connections between the various conceptual ideas of translation, drawn from literature and philosophy, and science are described.